Biochemical Characterization of a Regulatory Cascade Controlling Transcription of the Pseudomonas aeruginosa Type III Secretion System - Zheng, Zhida; Chen, Guozhou; Joshi, Shreyas; Brutinel, Evan D.; Yahr, Timothy L.; Chen, Lingling (The Journal of biological chemistry, 2007)
Many Gram-negative pathogens utilize type III secretion systems (T3SS) to translocate effector proteins into eukaryotic host cells. Expression of T3SS genes is highly regulated and is often coupled to type III secretory activity. Transcription of the Pseudomonas aeruginosa T3SS genes is coupled to secretion by a cascade of interacting regulatory proteins (ExsA, ExsD, ExsC, and ExsE). ExsA is an activator of type III gene transcription, ExsD binds ExsA to inhibit transcription, ExsC inhibits ExsD activity, and ExsE inhibits ExsC activity. The entire process is coupled to secretion by virtue of the fact that ExsE is a secreted substrate of the T3SS. Changes in the intracellular concentration of ExsE are thought to govern formation of the ExsC-ExsE, ExsC-ExsD, and ExsD-ExsA complexes. Whereas formation of the ExsC-ExsE complex allows ExsD to bind ExsA and transcription of the T3SS is repressed, formation of the ExsC-ExsD complex sequesters ExsD from ExsA and transcription of the T3SS is induced. In this study, we characterized the self-association states of ExsC, ExsD, and ExsE and the binding interactions of ExsC with ExsE and ExsD. ExsC exists as a homodimer and binds one molecule of ExsE substrate. Dimeric ExsC also interacts directly with ExsD to form a heterotetrameric complex. The difference in binding affinities between the ExsC-ExsE (Kd 1 nm) and ExsC-ExsD (Kd 18 nm) complexes supports a model in which ExsC preferentially binds cytoplasmic ExsE, resulting in the inhibition of T3SS gene transcription.